The difference of tensile bond strength between total etch and self etch dentin bonding on dentin surface - Adioro Soetojo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
Total etch dentin bonding agents had been used extensively in operative dentistry. These materials were used on dentin surfaces before application of the resin adhesive restorative. The purpose of this research was to prove the difference of tensile bond strength between total etch and self etch dentin bonding agent on dentin surface. The manner of preparing total etch dentin bonding agent was : bovine dentin as sample was grounded to give flat surface which was then etched with 37% phosphoric acid for 15 seconds, washed with 20 ml water and dried with blot dry technique. Sample was placed in a desiccator for one hour 60% humidity covered with bonding agent and put into tensile tool plunger and stored at room temperature (± 28 °C) for 24 hours. Sample was tested using Autograph instrument. The manner of preparing self etch dentin bonding was equal with total etch manner but without acid etching, washing and drying. The data analyzed using One-Way ANOVA test at α = 0.05 and followed Tukey HSD test. The result indicated that the tensile bond strength of total etch was higher than self etch dentin bonding at 60% humidity (p ≤ 0.05). In conclusion, the total etch dentin bonding agent with acetone solvents have a higher tensile bond strength compared with self etch dentin bonding agent also with dentin bonding in alcohol solvents.